Antimicrobial Peptide LL-37 Facilitates Intracellular Uptake of RNA Aptamer Apt 21-2 Without Inducing an Inflammatory or Interferon Response - Macleod, Tom; Ward, Joseph; Alase, Adewonuola A.; Bridgewood, Charlie; Wittmann, Miriam; Stonehouse, Nicola J. (Frontiers in Immunology, 2019)
RNA aptamers are synthetic single stranded RNA oligonucleotides that function analogously to antibodies. Recently, they have shown promise for use in treating inflammatory skin disease as, unlike antibody-based biologics, they are able to enter the skin following topical administration. However, it is important to understand the inflammatory milieu into which aptamers are delivered, as numerous immune-modulating mediators will be present at abnormal levels. LL-37 is an important immune-modifying protein upregulated in several inflammatory skin conditions, including psoriasis, rosacea and eczema. This inflammatory antimicrobial peptide is known to complex nucleic acids and induce both inflammatory and interferon responses from keratinocytes. Given the attractive notion of using RNA aptamers in topical medication and the prevalence of LL-37 in these inflammatory skin conditions, we examined the effect LL-37 had on the efficacy and safety of the anti-IL-17A RNA aptamer, Apt 21-2. LL-37 was demonstrated to complex with the RNA aptamer by electrophoretic mobility shift and filter binding assays. In contrast to free Apt 21-2, LL-37-complexed Apt 21-2 was observed to efficiently enter both keratinocytes and fibroblasts by confocal microscopy. Despite internalisation of LL-37-complexed aptamers, measurement of inflammatory mediators and interferon stimulated genes showed LL-37-complexed Apt 21-2 remained immunologically inert in keratinocytes, fibroblasts, and peripheral blood mononuclear cells including infiltrating dendritic cells and monocytes. The findings of this study suggest RNA aptamers delivered into an inflammatory milieu rich in LL-37 may become complexed and subsequently internalised by surrounding cells in the skin. Whilst the results of this study indicate delivery of RNA aptamers into tissue rich in LL-37 should not cause an unwarranted inflammatory of interferon response, these results have significant implications for the efficacy of aptamers with regards to extracellular vs intracellular targets that should be taken into consideration when developing treatment strategies utilising RNA aptamers in inflamed tissue.